Tertiary Treatment of Sugar Mill Effluent from Indigenously Developed Cation Exchanger from Agricultural Waste Wheat Straw: Utilization of Agricultural Waste for Sustainable Water Treatment and Irrigation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recycling and reuse of industrial effluents in agriculture is not only helpful for conserving the water for irrigation, also the plant nutrients. So it is essential that the amplifications of the use of industrial effluents in the crop field and their effect should be assessed before recommending for irrigation. The treated effluent did not cause an adverse effect on physico-chemical properties of soil. Waste water from sugar mill is properly treated and could be successfully used for irrigation, it is possible to prevent river waste pollution and also to augment already scare irrigation water resources. Utilization of agricultural waste i.e. wheat straw for large scale production of SWS ion exchanger is the need of the hour and exploring the possibility of its use in the treatment of various industrial effluents and use of treated effluents for irrigation is a meaningful proposition. Heavy Metal Analysis of Marigold Plant Irrigated with Treated Sugar Mill Effluent with SWS at Varying Dilution (Cu 0.135-0.278)